IMPLEMENTASI SISTEM PERTANIAN ORGANIK DENGAN PEMAKAIAN PUPUK KOMPOS SAMPAH ORGANIK DESA PADA PAKCOY - Miswanto Miswanto; Fitra Syawal Harahap; Hilwa Walida; Yusmaidar Sepriani (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2022)
The Karya Bakti farmer group is one of the farmer groups in the Tebing Tinggi, rankan subdistrict, Labuhanbatu Regency. Village waste compost containing various organic elements that can be used as a substitute for chemical fertilizers. The purpose of this service activity is to increase understanding and knowledge about organic farming systems by applying solid organic fertilizer to pakcoy plants and how to make organic waste compost. Carried out through socialization, and training related to the application of compost to pakcoy and the manufacture of village waste compost. The demonstration plot was focused on the correct workings and techniques in supporting the production of pakcoy through the application of organic waste compost. The production of pakcoy cultivation has been succesful even thoug it has not involved all members of the farmer group. Knowledge and skills of farmers have increased regarding the cultivation of pakcoy plants and processing of village waste into solid organic fertilizer and its application to pakcoy plants. The introduction of organic waste compost in pakcoy cultivation received a positive response from some members of the Karya Bakti farmer’s group and farmers have understood the procedures for processing village waste into solid organic fertilizer (compost) and its application to pakcoy plants.